2017
DOI: 10.1007/s11695-017-2687-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three-Dimensional Laparoscopy in a Bariatric Surgery Program: Influence in the Learning Curve

Abstract: The use of 3D laparoscopy in bariatric surgery in our center has helped reducing the operating time and hospital stay, and improving the safety of the surgery, either in GB or SG, being equally favorable in novice or more experienced surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…The superiority of 3D over 2D laparoscopy was observed at early and later stages in the learning curve . In Polish and Dutch studies , the involvement of residents in training with an experienced teacher does not compromise complication rates or weight‐reduction outcomes after bariatric surgery. On the other hand, mastery refers to having outcomes significantly better than the average surgeon, whereas competency (the learning curve figure discussed above) refers to having outcomes comparable to the average surgeon.…”
Section: Executive Summarymentioning
confidence: 97%
“…The superiority of 3D over 2D laparoscopy was observed at early and later stages in the learning curve . In Polish and Dutch studies , the involvement of residents in training with an experienced teacher does not compromise complication rates or weight‐reduction outcomes after bariatric surgery. On the other hand, mastery refers to having outcomes significantly better than the average surgeon, whereas competency (the learning curve figure discussed above) refers to having outcomes comparable to the average surgeon.…”
Section: Executive Summarymentioning
confidence: 97%
“…Guebbels et al (379) found that bariatric surgery learning curves depend on mentorship and improve as the preceding surgeon's skill improves. The superiority of 3D over 2D laparoscopy was observed at early and later stages in the learning curve (380). In Polish (381) and Dutch studies (382), the involvement of residents in training with an experienced teacher does not compromise complication rates or weight-reduction outcomes after bariatric surgery.…”
Section: R5 (2019*)mentioning
confidence: 97%
“…Literature search yielded 656 articles. Through the screening, 3 RCTs [106-108], 3 retrospective cohort studies [113,114,124] and 2 meta-analyses [68,94] were included in this review. The subjects of surgical procedures were hiatal hernia repair in 1 RCT, 1 bariatric surgery in 1 RCT and 1 retrospective cohort study, gastric cancer surgery in 1 RCT and 1 retrospective study, and esophagectomy in 1 retrospective study, respectively.…”
Section: D Laparoscopy In Sleeve Gastrectomy Offers No Advantage Over...mentioning
confidence: 99%